Selected Lectures of the Workshop of Pediatrics in collaboration with the Italian Society of Pediatric Allergology and Immunology (SIAIP); Cagliari (Italy); October 20, 2023 - - (Hygeia Press di Corridori Marinella, 2023)
Selected Lectures of the Workshop of Pediatrics in collaboration with the Italian Society of Pediatric Allergology and Immunology (SIAIP); Cagliari (Italy); October 20, 2023. The Meeting "Workshop of Pediatrics" is a Satellite Meeting of the 19th International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 18th-21st, 2023. The Meeting has been organized in collaboration with the Italian Society of Pediatric Allergology and Immunology (Società Italiana di Allergologia e Immunologia Pediatrica - SIAIP). LECT 1. LONG SHADOW OF COVID-19 IN CHILDREN AND ADOLESCENTS • D.A. Pleșca (Bucharest, Romania) LECT 2. A "BREATH OF HOPE": NEW INSIGHTS ON PEDIATRIC SEVERE ASTHMA IN THE OMICS ERA • B. Andrenacci, A. Licari, G.L. Marseglia (Pavia, Italy) LECT 3. THE "OMNIPOTENT" VITAMIN D • M. Miraglia del Giudice, A. Klain, G. Dinardo, C. Indolfi (Naples, Italy) LECT 4. CORRELATION BETWEEN ORAL AND LUNG MICROBIOTA • B. Polito, D. Peroni (Pisa, Italy) LECT 5. INSECTS IN THE DISH: FUTURE OR PRESENT? • A. Martelli (Milan, Italy) LECT 6. TUBERCULOSIS IN CHILDREN: A FORGOTTEN DISEASE? • U. Pelosi (Iglesias, Italy) LECT 7. CYSTIC FIBROSIS: FROM CLINIC TO METABOLOMICS • M. Zanda (Cagliari, Italy) LECT 8. PERIODIC FEVER, APHTHOUS STOMATITIS, PHARYNGITIS, ADENITIS (PFAPA): WHAT WE LEARNED AND WHAT METABOLOMICS TEACHES US • S. Leonardi (Catania, Italy) LECT 9. PEDIATRIC ALLERGY HIGHLIGHTS • R. Bernardini, S. Gracci (Empoli, Italy) LECT 10. EXPERIENCES FROM REAL WORLD PRACTICE IN THE LOW DOSE APPROACH TO SEASONAL ALLERGIC RHINITIS • A. Arrighi (San Giovanni Valdarno, Italy) LECT 11. METABOLOMICS IN CLINICAL PRACTICE • C. Marzetti (Bologna, Italy) LECT 12. PEDIATRIC AND NEONATOLOGY ATLAS THROUGH IMAGES • S. Vendemmia, M. Vendemmia (Aversa and Naples, Italy)